Clinical simulation to enhance undergraduate medical education and training at the University of the Free State - Labuschagne, Mathys Jacobus (University of the Free State, 2012)
An in-depth study was carried out with a view t compile recommendations for the use of clinical simulation as enhancement of undergraduate medical education and training at the University of the Free State. Clinical simulation plays an important role in the development of clinical skills and competence, and in creating a safe environment where students can learn without harm to patients while improving clinical reasoning and multidisciplinary training. Clinical simulation must be fully integrated with the curriculum, so that students can move between theory, simulation- and clinical training continuously. Assessment of skills and competence is a key component in clinical simulation-enhanced teaching and learning. In this study, the potential of clinical simulation was investigated as enhancement of undergraduate medical education and training. The extent to which clinical simulation could address the problems related to a decreasing clinical training platform, change in case mix and the demand for more health care professionals was investigated. Clinical simulation was considered as a complementary asset to enhance teaching and learning at the School of Medicine, UFS. The research methods comprised literature reviews, semi-structured interviews, focus group interviews, and observations during international visits. The literature review provided a background for a conceptual framework and contextualised the problem against related theory and research. Data were collected by means of semi-structured interviews with international experts to gain expert opinions on the use of simulation as teaching and learning tool, simulation-based assessment and the establishment of a simulation centre. Focus group interviews with lecturers and heads of departments at the UFS were conducted with the intent to evaluate the personal opinions and attitudes of the participants on these issues. The compilation of recommendations for the use of clinical simulation to enhance undergraduate medical education and training at the UFS and the planning and implementation of a simulation centre was achieved with the aid of the data collected. The premises, points of departure and role players were examined in order to make recommendations in this regard. The study originated from the recognition that a gap exists in the use of clinical simulation in the education and training of medical students at the UFS, but also in South Africa and the rest of Africa. To bridge the gap, the researcher compiled educational recommendations for the integration of clinical simulation as a required component and enhancement of the current curriculum. The development and implementation of a new simulation centre for the UFS School of Medicine was discussed in order to reach the goal of clinical simulation teaching and learning. A valuable contribution to knowledge was made by providing recommendations for developing and implementing a simulation centre for the School of Medicine, UFS. By developing the strategy, the identified gap is bridged, in that it can aid in integrating clinical simulation with current curricula, show how skills development and competence of medical students can improve and provide pointers for simulation-based assessment of medical students. Recommendations in this regard were made. The sound research approach and methodology ensured quality, reliability and validity. The completed research can form the basis for a further research undertaking.

‘n Diepgaande studie is onderneem met die doel om riglyne vir die gebruik van kliniese simulasie as versterking van voorgraadse mediese onderwys en opleiding aan die Universiteit van die Vrystaat (UV) daar te stel. Kliniese simulasie speel ‘n belangrike rol in die ontwikkeling van kliniese vaardighede en bedrewendheid, die skep van ‘n veilige omgewing waar studente kan leer sonder skade aan pasiënte asook die verbetering van kliniese redenasie, en multidissiplinêre opleiding. Kliniese simulasie moet ten volle geïntegreer word met die kurrikulum, sodat studente deurlopend tussen teorie, simulasie- en kliniese opleiding kan beweeg. Assessering van vaardighede en bedrewendheid is ‘n kern komponent van simulasie-versterkte onderrig en leer. In hierdie studie is kliniese simulasie ondersoek as versterking van voorgraadse mediese onderwys en opleiding om die probleme rakende die verkleinende opleidingsplatform, verandering in kliniese gevallesamestelling en die behoefte aan meer gesondheidspersoneel aan te pak. Kliniese simulasie is oorweeg as aanvullende modus om onderrig en leer by die Skool vir Geneeskunde by die UV te ondersteun. Die navorsingsmetodologie gevolg het bestaan uit ’n literatuuroorsig, semigestruktureerde onderhoude, fokusgroeponderhoude en waarnemings tydens internasionale besoeke aan simulasiesentrums. Die literatuuroorsig het as agtergrond gedien vir ‘n konseptuele raamwerk en om die probleem in die lig van toepaslike navorsing in verband te plaas. Data is ingesamel met behulp van semi-gestruktureerde onderhoude met internasionale kundiges met die doel om kundige opinies rakende die gebruik van simulasie as middel tot onderrig en leer, simulasie-gebaseerde assessering en die daarstelling van ‘n simulasiesentrum te bekom. Fokusgroeponderhoude is met dosente en departementshoofde van die Skool vir Geneeskunde is gevoer met die doel om die persoonlike sienings en houdings van die deelnemers oor die gebruik van simulasie te ondersoek. Die samestelling van aanbevelings vir die gebruik van kliniese simulasie om voorgraadse mediese onderwys en opleiding by die UV te versterk is bereik met behulp van die data wat ingesamel is. Die stellings, uitgangspunte en rolspelers is ondersoek met die doel om aanbevelings te maak rakende die gebruik van kliniese simulasie in hierdie opsig. Die studie het voortgespruit uit die identifisering van ‘n gaping in die gebruik van simulasie aan die UV, in Suid-Afrika en ook in die res van Afrika. Om die gaping te oorbrug, het die navorser onderwysaanbevelings vir die integrasie van kliniese simulasie as ‘n verpligte komponent en versterking van bestaande kurrikulums aanbeveel. Die ontwikkeling en implementering van ‘n nuwe simulasiesentrum vir die UV Skool vir Geneeskunde is bespreek met kliniese simulasie onderrig en leer as mikpunte. Die voorsiening van aanbevelings vir die ontwikkeling en implementering van ‘n simulasiesentrum vir die UV Skool vir Geneeskunde verteenwoordig ‘n waardevolle kennisbydrae. Die strategie oorbrug die gaping deurdat dit aandui hoe kliniese simulasie met die bestaande kurrikulums integreer kan word, vaardigheidsontwikkeling aangehelp kan word en simulasiegebaseerde assessering aangepak kan word. Die studie vervat aanbevelings hieroor. Die grondige navorsingsbenadering het kwaliteit, betroubaarheid en geldigheid verseker. Die afgehandelde navorsingsprojek kan die basis vir verdere navorsing vorm.
Thesis (Ph.D. (Health Professions Education))--University of the Free State, 2012
Keywords: Medicine -- Study and teaching (Higher) -- South Africa -- Bloemfontein; Medical education -- South Africa -- Bloemfontein; Medicine -- Study and teaching -- Simulation methods